Study on loneliness and depression of the institutionalized HIV/AIDS infected persons in Coimbatore - Kurian, Arun; Prathiba, N; Ranjit, L (International Journal of Engineering and Technology, 2018)
People living with HIV/AIDS are stigmatized which leads to isolation and loneliness. Loneliness may lead to distress and depression. The present study is an attempt to understand the influence of the loneliness on the depression of the HIV/AIDS infected people. A sample of 186 HIV/AIDS infected people were included for the study using a convenient sampling technique. The findings shows that the loneliness had a strong influence on the depression of the HIV/AIDS infected patients.Â Â